Viral Gene Therapy for Glioblastoma Multiforme: A Promising Hope for the Current Dilemma - Li, Junsheng; Wang, Wen; Wang, Jia; Cao, Yong; Wang, Shuo; Zhao, Jizong (Frontiers in Oncology, 2021)
Glioblastoma multiforme (GBM), as one of the most common malignant brain tumors, was limited in its treatment effectiveness with current options. Its invasive and infiltrative features led to tumor recurrence and poor prognosis. Effective treatment and survival improvement have always been a challenge. With the exploration of genetic mutations and molecular pathways in neuro-oncology, gene therapy is becoming a promising therapeutic approach. Therapeutic genes are delivered into target cells with viral vectors to act specific antitumor effects, which can be used in gene delivery, play an oncolysis effect, and induce host immune response. The application of engineering technology makes the virus vector used in genetic a more prospective future. Recent advances in viral gene therapy offer hope for treating brain tumors. In this review, we discuss the types and designs of viruses as well as their study progress and potential applications in the treatment of GBM. Although still under research, viral gene therapy is promising to be a new therapeutic approach for GBM treatment in the future.